2016
DOI: 10.1016/j.jesp.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of episodic thinking on altruism

Abstract: Episodic future thinking, which refers to the use of prospective imagery to concretely imagine oneself in future scenarios, has been shown to reduce delay discounting (enhance self-control). A parallel approach, in which prospective imagery is used to concretely imagine other’s scenarios, may similarly reduce social discounting (i.e., enhance altruism). In study 1, participants engaged in episodic thinking about the self or others, in a repeated-measures design, while completing a social discounting task. Redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 34 publications
4
13
0
Order By: Relevance
“…Through a gamble test, we found that red induced a more alternative-based process in information acquisition mode, which related to a more concrete logic compared with blue. This indicated that altruism is weakened in a more concrete mode of thinking, which is also consistent with previous conclusions (Yi et al, 2016). We showed these effects in two laboratory experiments (monetary donation and time donation).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Through a gamble test, we found that red induced a more alternative-based process in information acquisition mode, which related to a more concrete logic compared with blue. This indicated that altruism is weakened in a more concrete mode of thinking, which is also consistent with previous conclusions (Yi et al, 2016). We showed these effects in two laboratory experiments (monetary donation and time donation).…”
Section: Discussionsupporting
confidence: 92%
“…Different construal levels produce different consumer purchasing behaviors, even within the same choice set (Lynch and Zauberman, 2007). In a previous study of episodic future thinking, altruism was enhanced at high construal levels (Yi et al, 2016). The current research proved the effects of color on altruism, with the mediating variable being information acquisition.…”
Section: Introductionsupporting
confidence: 61%
“…Participants completed a computer‐administered social discounting task followed by a delay discounting task (modified from Yi et al, ). In the social discounting task, participants were asked to make a list of four different individuals: the person with whom they were closest ( P 1 ), a person with whom they were still close but not as close ( P 2 ), a person who they knew “kind of well” ( P 3 ), and a person they had met personally, but did not know well at all ( P 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to reward processing, discounting tasks also involve perspective taking. How participants assign subjective reward value in discounting tasks involves, in part, taking the perspective of either one's future self (delay discounting; Peters & Büchel, ) or another person (social discounting; Yi, Pickover, Stuppy‐Sullivan, Baker, & Landes, ). For example, prospective episodic thinking about oneself increases the willingness to wait for rewards (e.g., Daniel, Stanton, & Epstein, ; Lin & Epstein, ; Peters & Büchel, ), and brain regions linked to perspective taking are consistently implicated in both delay (Lempert, Speer, Delgado, & Phelps, ; Soutschek, Ruff, Strombach, Kalenscher, & Tobler, ) and social discounting (Strombach et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The emphasis has largely been on a link between the abilities to remember and imagine details for a specific place and time and a number of directive functions, such as planning and preparing for future decisions (e.g., Benoit, Gilbert, & Burgess, 2011;Peters & Büchel, 2010) and problem solving (see Schacter, 2012 for review). However, the social functions shared by remembering and imaging episodes have only recently begun to be examined (Merck, Topcu, & Hirst, 2016;Sheldon, McAndrews, & Moscovitch, 2011;Spreng & Mar, 2012;Yi, Pickover, StuppySullivan, Baker, & Landes, 2016).…”
Section: Introductionmentioning
confidence: 99%